Histopathological Analysis of Neck Muscles in Suicidal Hanging: A One-year Prospective Study - Gorchiya, Asharam; Mittal, Chaitanya; Vishwajeet, Vikarn; Suraj, Sundaragiri; Setia, Puneet (Journal of Forensic Medicine and Toxicology, 2025)
Hanging is the most common way used to commit suicide in India. The ligature mark is the main finding at the external examination, but the internal neck examination shows a very few visible findings on the gross examination. This study aimed to compare between gross features and histopathological findings in neck tissue and to analyze various micro scopic findings such as congestion, hemorrhage, muscle fiber breakdown, and leukocyte infiltration in the mylohyoid, sternohyoid, and sternocleidomastoid muscles. A total of 34 cases of suicidal hanging were taken for the study. There is a significant difference between gross features and histopathological findings in neck tissue. The congestion was found in sternohyoid and sternocleidomastoid muscles in 18 cases (52.94%) and 15 cases (44.11%), respectively, and was less evident in mylohyoid muscle only in 9 cases (26.47%). The hemorrhages were found in the sternocleidomastoid muscle in 16 cases (47.05%), in the sternohyoid muscle in 9 cases (26.47%), and in the mylohyoid muscle in 3 cases (8.82%). The muscle fiber breakdown was present in sternocleidomastoid muscle in 19 cases (55.88%), in sternohyoid muscle in 16 cases (47.05%), and mylohyoid in 11 cases (32.35%). The leukocyte infiltration is seen in only one case in the sternohyoid muscle. All the above findings were absent only in 4 cases (11.76%). Microscopic examination, particularly of anterior neck muscles, can become significant evidence of the antemortem nature of hanging in cases when gross vital signs are absent.